Corporate payout, cash retention, and the supply of credit: Evidence from the 2008–2009 credit crisis - Bliss, Barbara A.; Cheng, Yingmei; Denis, David J. (Journal of Financial Economics, 2015)
We document significant reductions in corporate payouts-both dividends and (to a larger extent) share repurchases-during the 2008–2009 financial crisis. Payout reductions are more likely in firms with higher leverage, more valuable growth options, and lower cash balances, i.e., those more susceptible to the negative consequences of an external financing shock. Moreover, firms appear to use the proceeds from the reduction in payout to maintain cash levels and to fund investment. These findings are consistent with the view that a shock to the supply of credit (net of demand effects) during the financial crisis increased the marginal benefit of cash retention, leading some firms to turn to payout reductions as a substitute form of financing.